Tenun Cag-Cag Sembiran Sebagai Representasi Cultural Capital dan Pengembangan Pariwisata Budaya Bali Utara - Putu Agustiantini (Jayapangus Press, 2026)
The minimalist esthetics of the cag-cag weave serves as a catalyst toward a complex system of meaning. In the context of sustainable tourism, cag-cag can be converted into authentic and transformative travel experiences, while also serving as a defense against cultural homogenization. The novelty of the research lies in the focus on micro-variant analysis of the weaving of Sembiran Village as a cultural and tourism sustainability. The research objectives are to interpret the cultural meaning, motifs, colors, and weaving techniques, and cultural capital-based tourism in North Bali. This research is based on ethnography, aiming to holistically understand the socio-cultural phenomenon of cag-cag weaving from the perspective of cultural practitioners. In the context of cag-cag weaving, simple lines are markers that refer to signs within the cosmology of the Sembiran community. Its interpretation is the essence of a straight line as a way of life and cosmology. The research findings indicate that the motif of elongated and straight lines is interpreted as a metaphor for the journey of human life, which must be straight and purposeful. Life should be like this line, not crooked, not deviating from the path established by our ancestors and customary rules. Furthermore, in tourism development strategies, cag-cag weaving not only focuses on commercial aspects, but also on creating sustainable value for cultural preservation, community well-being, and the tourist experience. The theoretical framework of Community-Based Tourism (CBT) and Creative Tourism serves as the main foundation for formulating this strategy, with the core principle that local communities must be the owners, managers, and primary beneficiaries of tourism activities.